Cutaneous limphoma in acquired f mmunodeficiency syndrome - Rosati, José Luís R.; Cantarino, Sonia; Ferreira, Myriam; Estrella, Rogério R.; Rorofino, Renata; Manaia, Jorge (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Toe authors present a case of cutaneous limphoma in paticnt with acute immunodcficiency syndrome. There was involvement of retroperitoncal and inguinal lymph nodes. besides involvement of lhe skin of lhe abdomen and lowcr limbs. Biopsy showcd large cell lymphoma. Thc course was fulminant, with death oc curring few days aftcr admission. Atypical cutaneous lcsions in HIV patients cspecially glossy crythcmatous tumors should raise thc suspicion of cutaneous lymphoma.